2007
DOI: 10.1017/s0031182007003691
|View full text |Cite
|
Sign up to set email alerts
|

Halfway up the trophic chain: development of parasite communities in the sparid fish Boops boops

Abstract: We examined the patterns of composition and structure of parasite communities in the Mediterranean sparid fish Boops boops along a gradient of fish sizes, using a large sample from a single population. We tested the hypothesis that species forming the core of the bogue parasite fauna (i.e. species which have a wide geographical range and are responsible for recognizable community structure) appear early in the fish ontogeny. The sequential community development observed supported the prediction that core speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Fish families were grouped by cage, so the relatively large effect of cage suggests that spatial variation in exposure and/or genetic susceptibility are more important for shaping parasite communities than the interactions between parasite species within a host. Indeed, several studies have found host age or size, factors that influence exposure rates, to affect parasite community structure (Vidal-Martinez, Kennedy & Aguirre-Macedo 1998;Poulin & Valtonen 2001;Zelmer & Arai 2004;P erez-del Olmo et al 2008;Timi, Luque & Poulin 2010). Our results also suggest that interspecific interactions can be obscured by intraspecific variation.…”
Section: Discussionsupporting
confidence: 58%
“…Fish families were grouped by cage, so the relatively large effect of cage suggests that spatial variation in exposure and/or genetic susceptibility are more important for shaping parasite communities than the interactions between parasite species within a host. Indeed, several studies have found host age or size, factors that influence exposure rates, to affect parasite community structure (Vidal-Martinez, Kennedy & Aguirre-Macedo 1998;Poulin & Valtonen 2001;Zelmer & Arai 2004;P erez-del Olmo et al 2008;Timi, Luque & Poulin 2010). Our results also suggest that interspecific interactions can be obscured by intraspecific variation.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, as the values of epidemiological parameters for this parasite were high, it is possible to conclude that L. excisum is a common inhabitant of this fish species in the studied area. However, it is unlikely that this constitutes an enlargement of the parasites host range as L. excisum (i) has been previously described as a generalist by Pérez-Del Olmo et al (2008), and (ii) has been reported parasitizing the related fish species T.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 96%
“…This can happen if small differences in the exposure to parasites occurring at early stages generate large intraspecific differences, while the parasite community of larger individuals might become more homogeneous through repeated parasite exposure, as commonly observed in other aquatic organisms 67 , 68 . However, parasites appearing in early stages might become dominant over time, leading to the homogenization of parasite communities in larger individuals 69 . Homogenization of parasite communities in larger G. pulex individuals might also be favored by cannibalism and size-selective predation, the latter of which might be connected with the removal of large infected individuals (e.g., by predatory fish) and/or small infected individuals (e.g., by predatory macroinvertebrates such as dragonfly larvae) or by a combination of both 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%